2016
DOI: 10.1002/chem.201603801
|View full text |Cite
|
Sign up to set email alerts
|

Dioxoiodane Compounds as Versatile Sources for Iodine(I) Chemistry

Abstract: The general synthesis, isolation and characterization of electrophilic iodine reagents of the general formula R N[I(O CAr) ] is reported. These compounds are air- and moisture-stable iodine(I) reagents, which were characterized including X-ray analysis. They represent conceptually new iodine(I) reagents with anions as stabilizers. These compounds display the expected performance as electrophilic reagents upon interaction with electron-rich substrates. The performance of these compounds in a total of 47 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
1
29
0
1
Order By: Relevance
“…60 Analogous dioxoiodane reagents [R-COO-I-OOC-R] + possessing a three-center halogen bond with oxygen as a halogen bond acceptor, [O-I-O] À , have also been reported to be applicable in halocyclization reactions. 61 Furthermore, the 62 Asymmetric halocyclisations using 3-center halogen bond complexes have also been attempted, yet have so far mostly given low enantioselectivities (o15%, Fig. 23), 63,64 most likely due to the large distance of the reaction centre, that is I + (A and B in Fig.…”
Section: Applications In Organic Synthesismentioning
confidence: 99%
“…60 Analogous dioxoiodane reagents [R-COO-I-OOC-R] + possessing a three-center halogen bond with oxygen as a halogen bond acceptor, [O-I-O] À , have also been reported to be applicable in halocyclization reactions. 61 Furthermore, the 62 Asymmetric halocyclisations using 3-center halogen bond complexes have also been attempted, yet have so far mostly given low enantioselectivities (o15%, Fig. 23), 63,64 most likely due to the large distance of the reaction centre, that is I + (A and B in Fig.…”
Section: Applications In Organic Synthesismentioning
confidence: 99%
“…Moreover, for the iodination of enamides using the PIFA/KI combination we had already shown that the observed reactivity is more akin to the one induced by acetoxyhypoiodite [13]. Alternatively, the involvement of an ammonium-complexed halogen(I) species of type n -Bu 4 N[X(O 2 CCF 3 ) 2 ], as described by Kirschning [28] and later Muniz [29] cannot be ruled out although, to the best of our knowledge, it has yet to be characterized for X = Cl. Regardless of the actual halogenation species involved, regioselective halogenation of the terminal double bond of 1 would then give bridged halonium 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Bis(acyloxy)iodate(I) anions are a class of hypervalent iodine compounds that are gaining increasing attention in synthetic organic chemistry as iodination reagents . Their synthetic utility is a consequence of the labile I−O bonds, the breaking of which results in the formation of reactive hypoiodite species.…”
Section: Figurementioning
confidence: 99%
“…The complexes are further stabilized by the C−H⋅⋅⋅O interactions between the methine hydrogen atoms of the macrocycle and oxygen atoms of the guests. The O−I bonds are 2.20 Å long, as found for other bis(acyloxy)iodates(I) . The two oxygen atoms bound at the iodine are 4.40 Å apart, accounting for only a 0.23 Å shorter distance from the center of the BU cavity in comparison to the 2:1 BU complexes with carboxylates .…”
Section: Figurementioning
confidence: 99%